Tren Akuntansi Islam di Indonesia: Perkembangan, Implementasi dan Tantangan - Dalimunthe, Razi Azwar Syahbuddin (Jurnal Ekonomi & Bisnis, 2025)
This article examines the development of Islamic Accounting trends in Indonesia, including its implementation, challenges, and development opportunities. The study discusses a key issue in the development of Islamic Accounting in Indonesia, namely the mismatch between the continuously evolving regulations and their actual implementation in Islamic financial institutions. As the country with the largest Muslim population in the world, Indonesia holds a strategic position in the development of Islamic Accounting that aligns with sharia principles. In terms of development, Islamic Accounting has made significant progress since its introduction in the early 1990s. Various Islamic financial institutions and universities have begun to adopt accounting standards that comply with sharia principles, including PSAK 101, 102, and 105 issued by the Indonesian Institute of Accountants (IAI). From an implementation perspective, the practice of Islamic Accounting in Indonesia shows that many companies have adopted sharia-based accounting systems, especially in the banking and financial sectors. However, there are some discrepancies in the application of sharia principles among different institutions, which may affect the transparency and accountability of financial reporting. Nevertheless, Islamic Accounting in Indonesia faces considerable challenges. These include a lack of understanding of sharia principles among accountants, limited availability of competent human resources, and the need to align sharia accounting regulations with international standards. Overall, the trend of Islamic Accounting in Indonesia shows great potential for growth, but it requires attention and support from various stakeholders to overcome existing challenges. This study is expected to provide insights for stakeholders in strengthening the practice of Islamic Accounting in Indonesia.